Central and Eastern Europe : roads to growth : papers presented at a seminar held in Baden, Austria, April 15-18, 1991 - Winckler, Georg (Washington : International Monetary Fund ; [Vienna] : Austrian National Bank, 1992)
The experience of Central and Eastern European countries with moving from centrally planned to open-market economies is examined in this collection of papers given at an April 1991 seminar, moderated by Georg Winckler and organized by the IMF and the Austrian National Bank.
Includes bibliographical references.
oif 01/08/16, rpm 01/09/16
Loans
Keywords: Business & economics / economic conditions; Business & economics / economic history; Business & economics / economics / comparative; political science / political economy; Europe, Central; Europe, Eastern